PENGARUH KOMPENSASI DAN MOTIVASI TERHADAP KINERJA KARYAWAN PT BANK EKONOMI RAHARJA TBK AREA JAKARTA 5 - Hesti Maheswari; Lulu Rehande Lutvy (Jurnal Manajemen., 2015)
This Research Entitlethe Effect Of Compensation And Motivation On Employee Performance. The Data Obtained Through The Survey By Distributing Questionnaires To 69 Respondents At Pt. Bank Ekonomi Raharja, Tbk Area Jakarta 5. The Sampling Technique Use Dissaturated Sampling, Whereas The Method Of Analysis Used Is Multiple Linear Regression Analysis And Hypothesis Testusing The T-Testfor Testing The Partiallyand F-Testfor Testing The Effect Of Simultaneously Using Spss Software Version 20. The Result Of The Research Showed That Compensation And Motivation Has Influence On Employee Performance Simultaneously. Partially, Compensation Has Influence On Employee Performance Whereas Motivation Han’ts Influence On Employee Performance.